Factors Effect Development of Professional Competencies of Lecturers at Iran’s University of Applied Science and Technology - Kazemi, Noureddin (2020)
This study proposes different approaches and models to analyze the factors affecting the development of professional competencies of lecturers at the University of Applied Science and Technology (UAST) in Tehran Province by using the lecturers’ viewpoints. This is an applied-quantitative descriptive-correlational study. The statistical population included all the 14000 lecturers of the UAST in Tehran. The sampling standards were employed to select 384 participants as the research sample. Based on the conceptual model, the research questions and hypotheses were then addressed through a researcher-made questionnaire and the items extracted from the statistical sample. In the descriptive statistics, data description was presented through both contextual and primary variables; however, Pearson’s product-moment correlation coefficient, structural equation modeling, and factor analysis were employed in the inferential statistics to analyze the research hypotheses. According to the research data, effective teaching and skill training improvement of lecturers had the greatest and smallest impacts, respectively, on the development of their professional competencies at the UAST. The standardized beta coefficients of these two variables were reported to be 0.591 and 0.368, respectively.